Visceral adipose tissue, aortic distensibility and atherosclerotic cardiovascular risk across body mass index categories - Makhmudova, Umidakhon; Wild, Benjamin; Williamson, Alice; Steinhagen-Thiessen, Elisabeth; Langenberg, Claudia; Eils, Roland; Landmesser, Ulf; Sannino, Anna (European journal of preventive cardiology, 2025)
While obesity is a well-established risk factor for cardiovascular disease, the relationship between visceral obesity, as assessed by imaging modalities of visceral adipose tissue (VAT), and the risk of atherosclerotic cardiovascular disease (ASCVD) has been insufficiently explored in large-scale studies, particularly across different body mass index (BMI) categories. We aimed at investigating the association between VAT and aortic distensibility as well as risk of ASCVD and comparing the magnitude of VAT-aortic distensibility and VAT-ASCVD association across BMI groups.Leveraging data from the UK Biobank, we examined the association between body weight-normalized VAT (VAT-index, VATi), assessed via abdominal MRI (VATi-MRI) or dual-energy X-ray absorptiometry (DXA; VATi-DXA), and aortic distensibility (a direct local measure of aortic stiffness) as well as the risk of ASCVD over a median follow-up period of 4.7 years. The abdominal MRI sub-cohort of the UK Biobank included 36 829 individuals, among whom 28 888 individuals were additionally evaluated using DXA. VATi was associated with a decrease in ascending aortic distensibility [VATi-MRI adjusted beta = −0.05 (95% CI: −0.07 to −0.04, P < 0.001)]; [VATi-DXA adjusted beta = −0.04 (95% CI: −0.06 to −0.03, P < 0.001)] and increased risk of ASCVD [VATi-MRI: HR 1.16 (95% CI: 1.09-1.23, P < 0.001)]; [VATi-DXA: 1.21 (95% CI: 1.13-1.3), P < 0.001], adjusted for age, sex, socioeconomic status, lifestyle factors, and cardiometabolic comorbidities. Across BMI categories, these associations were more pronounced in non-obese individuals. The cumulative incidence of ASCVD was higher in individuals with high VATi compared with those with low VATi, consistently observed across BMI categories. With a total of 1461 ASCVD events, incidence rates were higher in individuals with high VATi-MRI (VATi-DXA) compared with low VATi across all BMI categories: 5.3% (5.5%) vs. 2.2% (2.2%) in the normal BMI group, 5.5% (5.7%) vs. 2.5% (2.4%) in the overweight group, and 5.7% (5.9%) vs. 2.1% (2.1%) in the obese group (P log-rank <0.001). Overall, in the multivariable-adjusted Cox proportional hazard model, VATi was associated with increased ASCVD risk, but this association was attenuated when adjusted for the clinical marker of central obesity, the waist-to-hip ratio (WHR). In contrast, the association remained significant in the normal BMI group even after adjusting for WHR [HR for VATi-MRI 1.22 (95% CI: 1.06-1.42, P < 0.01); VATi-DXA 1.35 (95% CI: 1.11-1.65, P < 0.01)].Visceral obesity, measured by advanced imaging modalities, is linked to greater aortic stiffness and elevated risk of ASCVD, independent of BMI, in individuals without known ASCVD. Notably, these associations were observed mostly in non-obese subjects, with the strongest associations found in the normal BMI group. These findings highlight the additional predictive value of visceral obesity over general measures like BMI or WHR, particularly among non-obese individuals.Visceral fat, stored deep in the abdomen around internal organs, plays a critical role in heart and vascular health. This study examined its impact on the risk of developing atherosclerotic cardiovascular disease (ASCVD), including heart attacks, strokes, peripheral vascular disease, and the elasticity of the aorta, known as aortic distensibility, a subclinical marker of atherosclerosis, hypertension, and vascular aging. We found that:Higher visceral fat levels were strongly linked to an increased risk of ASCVD, especially in individuals with a normal body mass index (BMI), suggesting that visceral fat poses risks not captured by traditional measures like BMI.Increased visceral fat was associated with reduced aortic distensibility, indicating stiffer blood vessels, which contribute to long-term cardiovascular complications.These findings underscore the critical role of visceral fat in cardiovascular health, particularly in individuals with a normal BMI.
Online ahead of print veröffentlicht: 18. Juli 2025
Gesehen am 20.01.2026